The adhesion force change of an experimental road vehicle - Jilek, Petr; Berg, Jan (Manufacturing Technology Journal, 2021)
The Article deals with the controlled influence of the adhesive force in contact of the road vehicle's wheel with the road. The first section shows how the adhesive force is reduced. The next step is the familiarization with the experimental vehicle with the Alternative SkidCar, where experimental measurements were carried out, assessment of the advantages and disadvantages of the experimental vehicle with the Alternative SkidCar and the drive on the sliding surface following the experimental test methods. The objective of the article is to determine how great the difference in vehicle behav-iour is when the adhesive force changes by modifying the radial reaction and the change in the coeffi-cient of adhesion.
Keywords: Adhesive force; Experimental measurement; Skid of the vehicle; Vehicle stability